The world's trading system in the post cold war era implications for public administration. - Sekwat, Alex; Lynch, Thomas D.B (1995)
"The authors of this article argue that the world is evolving into a regional bloc trading system with important public policy implications. Recent developments in North America and Europe suggest that regional integration is becoming an alternative approach to the multilateral trade deliberations under the auspices of the General Agreements on Tariffs and Trade (GATT). The reasons for the evolution are suggested in this article, and arguments are presented on how the negative implications of this trend in world trade can be countered effectively by constructive domestic and international government action"
Keywords: General Agreement on Tariffs and Trade (GATT); International economic relations; International trade